A Novel Application of Random Hysteresis Current Control Technique for Acoustic Noise and Vibration Reduction of PMSM Drive - Pindoriya, Rajesh M.; Yadav, Ajeet K.; Rajpurohit, B. S.; Kumar, R. (Conference record of the Industry Applications Conference, 2020)
This paper presents a novel application of Random Hysteresis Current Control (RHCC) based Pulse Width Modulation (PWM) technique for a Permanent Magnet Synchronous Motor (PMSM) drive to reduce Acoustic Noise and Vibration (ANV). The HCC PWM scheme is simple and robust in switching control, but it is subject to variable switching frequency. However, since its harmonic spectrum is not randomly distributed like those given by the random PWM scheme, the harmonic effects still exist. Among various available spread spectrum techniques, RHCC technique has recently applied for unipolar and bipolar PWM fed power electronics converters to reduce harmonics in voltage and currents, with promising results. The proposed RHCC technique brings a significant reduction in torque and current ripples, ANV in the motor thereby enhancing the performance of the complete drive system under operation. An appropriate simulation and experimental analysis have been carried out. Performance result shows the substantial reduction of torque and current ripple in the PMSM drive with the proposed RHCC based PWM technique.